Lessons Learned from the Design Process of a Learning Management System - Sevindik, Tuncay; Basal, Ahmet (ATLANTIS PRESS, 2013)
Distance education has been spreading throughout the world especially with the increase in ICT. Learning Management System (LMS) is one of the most important dimensions of this educational model. LMS is a software application used for the administration, documentation, tracking, reporting and delivery of the course content. This study will introduce the design process of LMS that was developed by Yildiz Technical University. Based on the lessons learned during and after the design of LMS, it is concluded that users are one of the most important assets of LMS for the improvement of these systems.
Keywords: Distance Education; Learning Management Systems; Software; Computer Science; Engineering